Managing Bipolar Disease Complicated with Psychosis in Conjunction with Polypharmacy, Parkinson’s Disease, and Multiple Comorbidities - Irizarry, Ricardo; Sosa Gomez, Ariel; Miles, Simeon; Tamayo Acosta, Jean (Case Reports in Psychiatry, 2022)
The lifelong prevalence of bipolar disorder in adults, including subsyndromal forms, has increased over the years in the United States. By contrast, neurodegenerative diseases such as Parkinson’s disease have demonstrated an age-related rise in prevalence. As the global population manages to live longer thanks to sociomedical developments, it is expected to observe a rise in the occurrence of comorbid neuropsychiatric disorders. Herein, we present the case and management regimen of a 51-year-old female patient with multiple comorbidities and in the presence of polypharmacy. She was diagnosed with Parkinson’s disease and bipolar disorder type I alongside multiple comorbidities; her polypharmacy and medical history presented a significant clinical challenge in managing her condition. This case report focuses on the pharmacologic management of neuropsychiatric disorders titrated to this patient’s particular needs, which were complicated by psychosis and comorbidities.